The Undiscovered Country: Essays in Canadian Intellectual Culture - Ian Angus (Cultural Dialectics, 2013)
In this sequence of essays, Ian Angus engages with themes of identity, power, and the nation as they emerge in contemporary English Canadian philosophical thought, seeking to prepare the groundwork for a critical theory of neoliberal globalization. The essays are organized into three parts. The opening part offers a nuanced critique of the Hegelian confidence and progressivism that has come to dominate Canadian intellectual life. Through an analysis of the work of several prominent Canadian thinkers, among them Charles Taylor and C. B. Macpherson, Angus suggests that Hegelian frames of reference are inadequate, failing as they do to accommodate the fact of English Canada